Pengaruh Suhu Awal dan Lama Penyeduhan terhadap Karakteristik Sensoris dan Warna Teh Putih Silver Needle (Camellia assamica) Produksi PT. Bali Cahaya Amerta - Putra, I Wayan Eggy Perdana; Wrasiati, Luh Putu; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): Desember, 2020)
White tea is obtained from the shoots of Camellia assamica tea which are very young and still curled, have very fine silvery-white hairs or silver, and are kept out of the sun during the plucking process. Silver needle white tea produced by PT. Bali Cahaya Amerta is an excellent product promoted as functional drink. This research aimed to know the influence of initial temperature, and brewing time on the sensory characteristics and the color of silver needle tea; to decide the best initial temperature and brewing time in producing silver needle white tea. The design of experiment in this research used completely randomized design of organoleptic test and randomized complet block factorial in color intensity test with two treatment factors. The first factor was the initial brewing temperature which consisted of three levels namely, 75 o ±1 0 C, 85 0 ±1 0 C, 95 0 ±1 0 C. The second factor was the brewing time which consisted of three levels namely, three minutes, six minutes, and nine minutes. The analyzed variable was organoleptic characteristics, such as hedonic (the whole receiver), color score, taste, as well as aroma and color intensity system L * , a*, b * . The result of the research showed that the initial temperature and brewing time as well as the interaction of the two has a very significant effect to the whole tested variables. The treatment using 95 0 C initial temperature and nine minutes of brewing time produced the best characteristic, in which the color 2.40 ± 0.64 (limpidly yellowish to yellowish), taste 4.24±0.43 (slightly sweet to sweet), aroma 4.48±0.51 (has a tea scent to extremely tea scent), the whole receiver 6.20±0.43 (like to extremely like), brightness level (L * ) 55.32±0.17, redness level (a * ) 16.32±0.17, yellowish level (b*) 36.37±0.10. Keywords : white tea, initial temperature, brewing time, organoleptic, color intensity.